Peran Sekolah Kreatif dalam Mengembangkan Psikomotorik Anak di Rumah Belajar Tanah Merah Bangkalan - Abdullah Abdullah (Universitas Islam Lamongan, 2020)
This reseach describes creative schools in developing the psychomotor of students in the Rumah BelajarTanah Merah Bangkalan . this research qualitative research and a case study approach. The results of this research, The creative school designed by Rumah Belajar the Tanah Merah Bangkalan Learning House has the potential to increase the psychomotor domain of children, because edutainment methods, facilities. The facilities a re in accordance with the conditions of children and various outdoor and indoor programs, giving children the freedom to freely create and innovate without having to be too strict by school rules. In essence, they can learn while playing, in creative schools new innovations are needed, especially in teaching methods and classroom design in order to be able to present the fruits of their work from the age of 3 years to the age of 9 years. Besides that, there is a practical learning pattern. The children are directly invited to understand the lesson by practicing the contents of existing lessons. Like understanding the body structure of fish, they are invited to see the fish being dissected in front of the class